Intestinal absorption and hepatic elimination of drugs in high‐fat high‐cholesterol diet‐induced non‐alcoholic steatohepatitis rats: exemplified by simvastatin. (20th November 2020) - Li, Ziwei; Zhang, Jun; Zhang, Yufeng; Zhou, Limin; Zhao, Jiajia; Lyu, Yuanfeng; Poon, Long Hin; Lin, Zhixiu; To, Kenneth Kin Wah; Yan, Xiaoyu; Zuo, Zhong
Abstract : Background and Purpose: Altered drug pharmacokinetics is a significant concern in non‐alcoholic steatohepatitis (NASH) patients. Although high‐fat high‐cholesterol (HFHC) diet‐induced NASH (HFHC‐NASH) rats could simulate the typical dysregulation of cholesterol in NASH patients, experimental investigation on the altered drug pharmacokinetics in this model are limited. Thus, the present study comprehensive investigates the nature of such altered pharmacokinetics using simvastatin as the model drug. Experimental Approach: Pharmacokinetic profiles of simvastatin and its active metabolite simvastatin acid together with compartmental pharmacokinetic modelling were used to identify the key factors involved in the altered pharmacokinetics of simvastatin in HFHC‐NASH rats. Experimental investigations via in situ single‐pass intestinal perfusion and intrahepatic injection of simvastatin were carried out. Histology, Ces1 activities and mRNA/protein levels of Oatp1b2/CYP2c11/P‐gp in the small intestine/liver of healthy and HFHC‐NASH rats were compared. Key Results: Reduced intestinal absorption and more extensive hepatic elimination in HFHC‐NASH rats resulted in less systemic exposures of simvastatin/simvastatin acid. In the small intestine of HFHC‐NASH rats, thicker intestinal wall with more collagen fibres, increased Ces1 activity and up‐regulated P‐gp protein decreased the permeability of simvastatin, accelerated the hydrolysis of simvastatin and promoted the efflux of simvastatin acid respectively. In the liver of HFHC‐NASH rats, higher hepatic P‐gp expression accelerated the hepatic elimination of simvastatin. Conclusion and Implications: Altered histology, Ces1 activity and P‐gp expression in the small intestine/liver were identified to be the major contributing factors leading to less systemic exposure of drugs in HFHC‐NASH rats, which may be applicable to NASH patients.